Inhibition of endothelial cell Ca2+ entry and transient receptor potential channels by Sigma‐1 receptor ligands. (25th February 2013) - Amer, Mohamed S; McKeown, Lynn; Tumova, Sarka; Liu, Ruifeng; Seymour, Victoria AL; Wilson, Lesley A; Naylor, Jacqueline; Greenhalgh, Katriona; Hou, Bing; Majeed, Yasser; Turner, Paul; Sedo, Alicia; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose The Sigma‐1 receptor (Sig1R) impacts on calcium ion signalling and has a plethora of ligands. This study investigated Sig1R and its ligands in relation to endogenous calcium events of endothelial cells and transient receptor potential (TRP) channels. Experimental Approach Intracellular calcium and patch clamp measurements were made from human saphenous vein endothelial cells and HEK 293 cells expressing exogenous human TRPC5, TRPM2 or TRPM3. Sig1R ligands were applied and short interfering RNA was used to deplete Sig1R. TRP channels tagged with fluorescent proteins were used for subcellular localization studies. Key Results In endothelial cells, 10–100 μM of the Sig1R antagonist BD1063 inhibited sustained but not transient calcium responses evoked by histamine. The Sig1R agonist 4‐IBP and related antagonist BD1047 were also inhibitory. The Sig1R agonist SKF10047 had no effect. Sustained calcium entry evoked by VEGF or hydrogen peroxide was also inhibited by BD1063, BD1047 or 4‐IBP, but not SKF10047. 4‐IBP, BD1047 and BD1063 inhibited TRPC5 or TRPM3, but not TRPM2. Inhibitory effects of BD1047 were rapid in onset and readily reversed on washout. SKF10047 inhibited TRPC5 but not TRPM3 or TRPM2. Depletion of Sig1R did not prevent the inhibitory actions of BD1063 or BD1047 and Sig1R did not co‐localize with TRPC5 or TRPM3. Conclusions and Implications The data suggest that two types of Sig1R ligand (BD1047/BD1063 and 4‐IBP) are inhibitors of receptor‐ or chemically activated calcium entry channels, acting relatively directly and independently of the Sig1R. Chemical foundations for TRP channel inhibitors are suggested.